Pelatihan Manajemen Pengelolaan Keuangan Kelompok Majelis Taklim Desa Simpang Tiga Rawang, Kota Sungai Penuh - Elvi Nilda; Bustami Bustami; Endah Sri Wahyuni; Samsul Bahry Harahap; Azhar Azhar; Eka Putra (Institut Agama Islam Negeri Kerinci, 2026)
This Community Service Program (PkM) aimed to improve the understanding and skills of the Majelis Taklim group in Simpang Tiga Rawang Village, Sungai Penuh City, in managing organizational finances effectively, transparently, and accountably. The main problems faced by the majelis taklim group were the limited ability of the administrators in financial recording, cash report preparation, budget planning, and monitoring the use of activity funds. The implementation method employed a participatory approach through several stages, including observation, needs identification, material delivery, practical training on preparing simple financial reports, discussions, and activity evaluation. The participants consisted of administrators and members of the majelis taklim group who actively participated in religious and social community activities. The results of the program indicated an increase in participants’ understanding of the importance of systematic and transparent organizational financial management. Participants were also able to prepare simple cash inflow and outflow records and understand the basic principles of activity budget planning. Furthermore, this activity encouraged the development of collective awareness in maintaining organizational financial accountability to increase the trust of members and the community. This training is expected to become an initial step in building a more professional and sustainable governance system for the majelis taklim organization.